Platygaster splendidula Ruthe 1859 ... - Awad, Jessica; Krogmann, Lars; Talamas, Elijah (Zenodo, 2023)
Platygaster splendidula Ruthe, 1859 Platygaster splendidulus Ruthe 1859: 313. Platygaster hirticornis Förster 1861: 42. Platygaster lissonotus Förster 1861: 42. Platygaster hirticornis Förster 1861 – Buhl 1996: 223, figs 7–9. Platygaster lissonota Förster 1861 – Dalla Torre 1898: 474. — Buhl 1996: 225, figs 13–15. Material examined ICELAND • 2 specimens, syntypes of Pl. splendidulus 19 Jun. 1856; [Standinger leg.]; NHMW NHMW-HYM#0005300. SWITZERLAND • 1 ♂, holotype of Pl. hirticornis Rosegg-Thal [Roseg Valley]; [Jul. 1861]; [A. Förster leg.]; NHMW NHMW-HYM#0005284 • 1 ♂, lectotype of Pl. lissonotus same data as for preceding; NHMW NHMW-HYM#0005282 • 1 ♂, paralectotype of Pl. lissonotus same data as for preceding; NHMW NHMW-HYM#0005283. ... : Published as part of Awad, Jessica, Krogmann, Lars & Talamas, Elijah, 2023, Taxonomic history and review of the Förster genera of Platygastridae (Hymenoptera: Platygastroidea), pp. 1-46 in European Journal of Taxonomy 875 (1) on page 29, DOI: 10.5852/ejt.2023.875.2137, http://zenodo.org/record/8047251 ...